An investigation into the syntactic and semantic features of verb phrases expressing victory and defeat in tennis commentaries in english and vietnamese - Bùi, Thị Nhung (2016)
his thesis investigates the semantic and syntactic features of verb phrases expressing victory and defeat in English and Vietnamese tennis commentaries. The study aims at investigating how writers comment as well as discovering similarities and differences of verb phrases expressing victory and defeat are used in tennis commentaries in English and Vietnamese. In order to achieve this aim, a combination of the descriptive, quantitative and qualitative approach was used to describe the syntactic and semantic features of verb In the study, 400 samples (200 samples in English and 200 samples in Vietnamese) in the tennis commentaries were selected for investigation. Semantically, instances of verb phrases were realized in Clause as Representation. The findings of the thesis show that instances of verb phrases were realized with linguistic structures such as verbal group as realization of material process: process of doing in the clause as exchange in both of nonphrasal verbs and phrasal verbs. Some similarities and differences in the way writers use verb phrases expressing victory and defeat in English and Vietnamese tennis commentaries were found. The research result is hoped to bring about some contributions to the readers, EFL students and teachers in comprehending and writing tennis commentaries in the two languages.